BREEDING PROGRAM FOR DEVELOPMENT OF DAIKON VARIETY IN CRIMEA - V. I. Nemtinov (Овощи России)
The breeding program for daikon in Crimea was carried out according to the following plan: the seed sowing in the third decade of July, and root selection for economically valuable traits after 58-70 days; storage during the winter; planting in the short warm periods of February, under temporary tunnel coverage for parental lines used for hybridization; seed production in second decade of July; seed sowing in third decade of July; assessment of progenies in 58-70 days. The annual cycle was repeated until the constant lines were obtained. As result of that, the middle-maturing variety was developed, the periods from shoots to root formation, to root harvesting, to seed maturation were 26 days, 63 days and 90 days, respectively. Variety ‘Solol’ had 3% less of dry matter than standard variety ‘Klyck Slona’ and 10% higher than standard variety ‘Guliver’. The variety ‘Sokol’ had 6-14% more total sugar than both standard varieties. The variety was characterized by high ultrastability and agrochemical stability (86%), average value of yield variation V=13.6%, whereas correlation with sum of effective temperature, r = -0.34 and sum of rainfall, r = +0.58. The yield of daikon root in the variety ‘Sokol’ was 47 t/ha that was 27-31% higher than yield in the standard variety.